2015
DOI: 10.1007/s11356-015-4426-6
|View full text |Cite
|
Sign up to set email alerts
|

Efficient secretory production of CotA-laccase and its application in the decolorization and detoxification of industrial textile wastewater

Abstract: Fungal laccases are typically unstable at high pH and temperature conditions, which limit their application in the decolorization of textile wastewater. By contrast, the highly stable bacterial laccases can function within a wider pH range and at high temperatures, thus have significant potential in treatment for textile wastewater. In our previous work, a thermo-alkali-stable CotA-laccase gene was cloned from Bacillus pumilus W3 and overexpressed in Escherichia coli. In this study, the robust CotA-laccase ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…It is well-known that redox mediators such as ABTS, HOBt, and some lignin-derived compounds sometimes enhance enzyme action dramatically 19 . However, significantly fewer efforts have been made to understand the potential decolorization activity of bacterial laccase-like MCOs, except for a spore coat laccase-like protein (CotA) of Bacillus spp 24 27 . In this study, we found that IOX, a novel MCO produced by an iodide-oxidizing bacterium Iodidimonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that redox mediators such as ABTS, HOBt, and some lignin-derived compounds sometimes enhance enzyme action dramatically 19 . However, significantly fewer efforts have been made to understand the potential decolorization activity of bacterial laccase-like MCOs, except for a spore coat laccase-like protein (CotA) of Bacillus spp 24 27 . In this study, we found that IOX, a novel MCO produced by an iodide-oxidizing bacterium Iodidimonas sp.…”
Section: Discussionmentioning
confidence: 99%
“…A wide array of compounds has been used in the literature as mediators, such as 2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO), ABTS ( [14], 1-hydroxybenzotriazole (1-HBT) [38], syringaldehyde, vanillin, α-naphthol [39], and others. The laccase-mediator system (LMS) has been used for the removal of residual lignin in biomass [13,40], or the treatment of recalcitrant pollutants, such as antibiotics [39] or other drugs [41], pesticides [42], industrial textile wastewater [43], and even synthetic fragrances [44]. LMS has been also used for the oxidative synthesis of platform chemicals [45].…”
Section: Structural Aspects Mode Of Action and Redox Properties Of mentioning
confidence: 99%
“…Spore coat protein A (CotA) from Bacillus subtilis, a 65 kDa protein (513 amino acids), is a high thermostable bacterial laccase [4]. The CotAlaccase has been reported for industrial textile wastewater detoxification and decolorization [5,6]. Low production yield of the native CotAlaccase limited the applications in industry.…”
Section: Introductionmentioning
confidence: 99%